Medizinhistorische Literatur [Medical history literature] - Bauer, Bruno (GMS Medizin – Bibliothek – Information, 2012)
[english] The focus of the current issue 1-2/2012 of GMS Medizin – Bibliothek – Information is on medical history literature. In six articles special collections and recent projects of medical history libraries in Berlin, Hamburg, Heidelberg, Leipzig, Vienna and Zurich are presented. The authors in this issue are Melanie Scholz & Vera Seehausen (From Augusta to Klingsor, from Luise to Benjamin – past, present and future of the library of the Institute of the History of Medicine in Berlin), Alexandra Veith (Library of the Institute for History of Medicine and Ethics of Medicine, Heidelberg), Melanie Kintzel, Meike Knittel & Tanja Krutky (Historic collections of the Medical Library of the University of the University Medical Center Hamburg-Eppendorf and their deacidification), Dagmar Geithner (Library of the Karl Sudhoff Institute for the History of Medicine and Science, Leipzig – a Historical Review), Harald Albrecht, Bruno Bauer & Walter Mentzel (The Josephinian Library and the medical-historic stock of the University Library of the Medical University of Vienna) and Monika Huber & Ursula Reis (Library of the Institute and Museum of the History of Medicine Zurich). [german] Schwerpunktthema der aktuellen Ausgabe 1-2/2012von GMS Medizin – Bibliothek – Information ist medizinhistorische Literatur. In sechs Beiträgen werden Bestände und aktuelle Projekte medizinhistorischer Bibliotheken in Berlin, Hamburg, Heidelberg, Leipzig, Wien und Zürich vorgestellt. Verfasst wurden die Beiträge der Schwerpunktausgabe von Melanie Scholz & Vera Seehausen (Von August zu Klingsor, von Luise zu Benjamin – Vergangenheit, Gegenwart und Zukunft der Bibliothek des Instituts für Geschichte der Medizin in Berlin), Melanie Kintzel, Meike Knittel & Tanja Krutky (Medizinhistorische Buchbestände am Universitätsklinikum Hamburg-Eppendorf und ihre Entsäuerung), Ara Veith (Bibliothek des Instituts für Geschichte und Ethik der Medizin in Heidelberg), Dagmar Geithner (Die Bibliothek des Karl-Sudhoff-Institutes für Geschichte der Medizin und der Naturwissenschaften in Leipzig – ein historischer Abriss), Harald Albrecht, Bruno Bauer & Walter Mentzel (Josephinische Bibliothek und medizinhistorische Bestände der Universitätsbibliothek der Medizinischen Universität Wien) und Monika Huber & Ursula Reis (Die Bibliothek des Medizinhistorischen Instituts und Museums der Universität Zürich).